(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The retail industry in India is revolutionizing due to notable changes in the overall structure. It has also observed that there are significant shifts in demographic characteristics of Indian retail customers, and it has considerable influence on the buying behavior and retail Industry. Store Commitment is nothing but to choose one store over others following an explicit and extensive evaluative process as a result of a consumer pledging. In this paper, various demographic factors, i.e., Gender, Marital status, Age, Education, and Income, were considered to find its influence on various store Commitment factors like Store Loyalty, Share of Wallet, Store Preference and Share of Visit. We surveyed retail customers who are a member of minimum one Multi-Partner Loyalty Program and across different retailers. For data analysis, we used Statistical Package for Social Science (SPSS-20). We used descriptive research design along with disproportionate-stratified Random Sampling for this study.